The effect of antenatal psychological well-being on maternal health status - Mays Shudayfat; Esra’ O. Taybeh; Mervat Alsous (PLoS ONE, 2025)
Background The presence of psychological pressures may negatively affect the health of pregnant women pre-, during, and post-childbirth and may lead to many complications. Aim The aim of the present study was to assess the psychological well-being among pregnant women in Jordan and to explore the relationship between psychological pressures and gestational health consequences. Method A cross-sectional study was performed with pregnant women at 24–28 weeks of gestation, who were recruited during maternity clinic visits at Mafraq and Princess Badea hospitals between February and July 2022. Data, including pre- and current gestational weight, height, and pre- and current body weight, were collected through a data collection form, along with a whole blood sample obtained at the clinic to measure fasting plasma glucose (FPG) and HbA1c levels. The Depression, Anxiety, and Stress Scale (DASS) was employed to assess the psychological well-being of the women. Results A total of 385 pregnant women participated in the study. The majority of pregnant women experienced a moderate level of depression (77.7%) and anxiety (74.5%), and around half experienced a moderate stress level (44.9%). FPG showed “normal” in 168 (43.6%) participants and “abnormal” in 217 (56.4%). However, the HbA1c level showed “normal” in 190 (49.4%) participants and “abnormal” in 195 (50.6%) with a significant correlation of 0.885. DASS with gestational diabetes mellitus showed a significant difference with a depression factor of p = 0.015, and anxiety factor of p = 0.010, while there was an insignificant difference with stress. One hundred and three (26.8%) participants showed normal weight gain while 282 (73.2%) showed abnormal weight, and there was an insignificant difference between DASS and weight. Conclusion The findings show a positive relation between DASS scores and the incidence of gestational diabetes mellitus (GDM). The study emphasizes the importance of further investigation and tailored interventions for depression and anxiety symptoms during pregnancy.